Methodology for ensuring occupational safety and health based on the assessment and management of occupational risks - Sviatskyi, V.; Свяцький, В. В. (ЦНТУ, 2025)
The draft Law of Ukraine “On Safety and Health of Workers at Work”, adopted in the first reading, clearly delineates the transition of national legislation to a risk-oriented model of occupational safety management. This transition holds strategic significance, as it is aimed at a profound transformation of the system for preventing occupational injuries and diseases through the implementation of systematic assessment, control, and risk management – key principles that have long formed the basis of approaches to occupational safety in developed EU countries and worldwide. The conducted analysis demonstrates that Ukraine is at a strategically important stage of modernizing its occupational safety system. The adoption of the law introducing a risk-oriented approach in the industrial sector represents a substantial step forward, where the assessment of occupational risks is gradually evolving from a formal procedure into a genuine tool for enhancing safety. Such development not only ensures compliance with European Union requirements but also lays the groundwork for the formation of truly safe working conditions, the advancement of a safety culture, professional education and national institutions in the field of occupational safety. Прийнятий у першому читанні проект Закону України «Про безпеку та здоров’я працівників на роботі» чітко окреслює перехід національного законодавства до ризик-орієнтованої моделі управління охороною праці. Такий перехід має стратегічне значення, оскільки спрямований на глибоку трансформацію системи запобігання виробничому травматизму та професійним захворюванням шляхом упровадження системного оцінювання, контролю та управління ризиками – ключових принципів, що давно стали основою підходів до безпеки праці в розвинених країнах ЄС та світу. Проект закону запроваджує низку важливих змін, серед яких: законодавче закріплення базових термінів у сфері охорони та гігієни праці, що раніше були відсутні у вітчизняній нормативній базі; перегляд розподілу відповідальності між роботодавцем і державою; оновлення механізмів державного нагляду за дотриманням законодавства про безпеку працівників на роботі. Такі нормативні зміни покликані забезпечити формування національної системи управління охороною праці, побудованої відповідно до європейських принципів запобігання, оцінювання, контролю та управління виробничими ризиками тощо.
Методологія забезпечення безпеки та гігієни праці на основі оцінки та управління професійними ризиками
Keywords: occupational safety and health; legislation; industrial risk; risk-based modeling techniques; безпека і гігієна праці; законодавство; виробничий ризик; методики ризик-орієнтованих моделей